PENGARUH PEMBERIAN NATRIUM HIDROKSIDA ( NaOH ) TERHADAP PERKEMBANGAN TELUR CACING Toxocara vitulorum - , PRIYO UTOMO; , Dr. drh. R Wisnu Nurcahyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was to determine the effect of Natrium Hydroxide (NaOH) to the development of Toxocara vitulorum egg. The research was carried out in the laboratory of Parasitology Faculty Veterinary Medicine Universitas Gadjah Mada. A number of seven petri dish ( No. 2 to No. 7 ) was filled with 5 ml solution contained 15 Toxocara vitulorum egg/ml. The petri dish No.2 to No.7 were treated by 0,5 % NaOH, 1 % NaOH, 2,5 % NaOH, 5 % NaOH, 7,5 % NaOH, and 10 % NaOH respectively. Petri dish No. 1 was as control. All petri dished then were incubated at 27O C for four weeks. The larvated a every petri dish were counted every week for four weeks. The data was analyzed descriptively. The research concluded that NaOH inhibited the development of Toxocara vitulorum egg in the first week.